2011
DOI: 10.1007/s11255-011-9967-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of newer unidirectional and bidirectional barbed suture on vesicourethral anastomosis during robot-assisted radical prostatectomy and its comparison with polyglecaprone-25 suture: an initial experience

Abstract: VUA with unidirectional barbed suture is safe and takes less time compared to monofilament suture as repeated cinching; help of assistance and knot tying are not required by virtue of its self-retaining characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 24 publications
2
41
1
Order By: Relevance
“…Ultimately, a total of 10 studies (comprising 378 cases and 369 controls) were included in our metaanalysis. [10][11][12][13][14][15][16][17][18][19] All the studies were published within the last 4 years, reflecting the increased application of this technique. Three studies were RCTs (LE, 2b) comparing BS and conventional sutures.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, a total of 10 studies (comprising 378 cases and 369 controls) were included in our metaanalysis. [10][11][12][13][14][15][16][17][18][19] All the studies were published within the last 4 years, reflecting the increased application of this technique. Three studies were RCTs (LE, 2b) comparing BS and conventional sutures.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies reported on postoperative urinary leak, 4 13,15,16,18 of which reported no urinary leak observed in either group. Meta-analysis of the remaining 5 studies 10,11,14,17,19 indicated no significant differences in postoperative urinary leak (OR, 0.57; 95% CI, 0.20-1.67; Bladder Neck Stricture and Anastomosis Stricture Substantial heterogeneity was observed across the set of 5 studies reporting on bladder neck stricture and anastomosis stricture, which prohibited a meta-analysis.…”
Section: Urinary Leak and Retentionmentioning
confidence: 99%
“…Postoperative VUA leakage is one of the most bothersome complications of radical prostatectomy, as it may result in poor anastomosis healing, urethral stricture, urinoma as well as abscess formation [3,5,6]. In an attempt to simplify this critical step of LRP, several authors have proposed different techniques for the VUA [7,8,9,10,11,16]. The single-knot running Van Velthoven method, which was introduced to the urological community in 2003, has been adopted by many laparoscopic surgeons, as it ensures the adequate formation of the VUA and consequently a good functional outcome [7,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The single-knot running Van Velthoven method, which was introduced to the urological community in 2003, has been adopted by many laparoscopic surgeons, as it ensures the adequate formation of the VUA and consequently a good functional outcome [7,11,12]. Other authors have promoted a single running suture in different formats [8,12,17]. Our laparoscopic single running suture technique differs from other methods because it uses a single absorbable suture placed 6 times through both the bladder neck and the urethra, with only 1 knot tied at the end of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation